Analysis of Work Network and Critical Trajectory on Penganten - Ngampal Road Reconstruction Project Using Critical Path Method (CPM) - Al-Putro, Akmal Puguh; Nugroho, Laksono Djoko; Muhammadun, Haris (Transpublika Publisher, 2025)
The Reconstruction Project of Penganten-Ngampal Road in Bojonegoro Regency faces challenges in time and resource management, leading to project delays. These delays affect time and cost efficiency, which are key issues in achieving the project's objectives. To address this problem, this study aims to analyze the project’s work schedule and critical path using the Critical Path Method (CPM). The research employs a quantitative method, with data collected through primary and secondary data sources. Primary data was obtained through field observations and questionnaires, while secondary data was gathered from project documents and relevant literature. Using CPM, the first step was to construct the project’s work schedule based on the work breakdown structure (WBS) and the relationships between activities. An analysis was then performed utilizing forward pass and backward pass methods to identify the critical path. This path comprises tasks that require timely completion to avoid causing additional project delays. The results show that the critical path for the Penganten-Ngampal Road Reconstruction Project is identified in activities with codes A, C, D, E, and F. The total project completion duration based on the analysis is 47 days. Activities on this critical path must be completed on time, as delays in any of these activities will affect the overall completion of the project. Therefore, better time management and proper resource allocation for critical activities are essential to complete the project according to the planned timeline.